A novel regenerative hydrogen cerium fuel cell for energy storage applications. Issue 18 (14th May 2015) - Hewa Dewage, H.; Wu, B.; Tsoi, A.; Yufit, V.; Offer, G.; Brandon, N.
<x xml:space="preserve">Abstract</x> A novel regenerative hydrogen cerium fuel cell is presented which has the potential to deliver both low cost and high performance.